Role of Feeling of Loneliness and Emotion Regulation Difficulty on Drug Abuse - Zahra Nikmanesh; Yahya Kazemi; Masoume Khosravi (Shahid Sadoughi University of Medical Sciences, 2015)
Introduction: The Risk behaviors such as drug abuse are prevalent anxiously in youth. Thus investigation and recognition of risk behaviors are important. The aim of the present study is to investigate on relationship between loneliness and the difficulty in emotional regulation with drug abuse. Materials and Methods: this research was descriptive- correlation. The sample was comprised of 452 students of University of Sistan and Baluchestan, Iran. Participants were selected by cluster sampling. The instruments were the Loneliness Scale , the Difficulty in Emotion Regulation Scale and the Drug Abuse . For statistical analysis, Pearson correlation and regression analysis methods were used. Results: The results show that there is a positive and significant relationship between loneliness and the difficulty in emotion regulation with drug abuse. The Enter regression analysis for prediction of the drug abuse shows that the loneliness predicts .09 and the difficulty in emotional regulation predicts .08 of the drug abuse variances (P≤ .05). Conclusion: Therefore, it is recommended to university and cultural instructional planners to pay attention to variables of loneliness and emotional regulation as drug abuse risk factors and introduce especial and preventer programs in this subject.